TYPES OF ADMINISTRATIVE PROCEDURES IN THE FIELD OF TAXATION: TODAY'S ISSUES (Bulletin of criminological association of Ukraine, 2024)
The scientific work carried out a scientific analysis of the positions of administrative scientists and the provisions of tax legislation, which made it possible to distinguish types of administrative procedures in the field of taxation depending on the powers of the State Tax Service bodies: 1) procedures for licensing and registration activities in the field of taxation; 2) control and supervision procedures in the field of circulation of excisable goods in Ukraine; 3) jurisdictional administrative procedures in the field of taxation. It is emphasized that each isolated administrative procedure in the field of taxation is completed by the adoption (approval) of an administrative act (decision), which can subsequently be appealed in accordance with the norms of current legislation in a judicial or extrajudicial manner.
Keywords: administrative procedure; procedure; legal procedure; public authorities; tax service bodies; taxation; types; classification